2015
DOI: 10.1371/journal.pntd.0003726
|View full text |Cite
|
Sign up to set email alerts
|

Insensitivity to the Spatial Repellent Action of Transfluthrin in Aedes aegypti: A Heritable Trait Associated with Decreased Insecticide Susceptibility

Abstract: BackgroundNew vector control paradigms expanding the use of spatial repellents are promising, but there are many gaps in our knowledge about how repellents work and how their long-term use might affect vector populations over time. Reported here are findings from a series of in vitro studies that investigated the plasticity and heritability of spatial repellent (SR) behaviors in Aedes aegypti exposed to airborne transfluthrin, including results that indicate a possible link between repellent insensitivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 48 publications
3
81
1
3
Order By: Relevance
“…Our study also observed significant resistance to both the toxicity and repellency of pyrethrum, transfluthrin, and metofluthrin in the PR strain, similar to that observed for transfluthrin in a selected pyrethroid‐resistant strain of Ae. aegypti by Wagman et al . Similarly, Kawada et al .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Our study also observed significant resistance to both the toxicity and repellency of pyrethrum, transfluthrin, and metofluthrin in the PR strain, similar to that observed for transfluthrin in a selected pyrethroid‐resistant strain of Ae. aegypti by Wagman et al . Similarly, Kawada et al .…”
Section: Discussionmentioning
confidence: 85%
“…30 Our study also observed significant resistance to both the toxicity and repellency of pyrethrum, transfluthrin, and metofluthrin in the PR strain, similar to that observed for transfluthrin in a selected pyrethroid-resistant strain of Ae. aegypti by Wagman et al 21 Similarly, Kawada et al 31 showed resistance to both contact repellency and lethality to permethrin and deltamethrin when tested on kdr-resistant Anopheles gambiae. In our study, the PR strain showed similar resistance in vapor and topical toxicity to these compounds, but showed different resistance ratios for repellency.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, distinct metabolic, knock-down and cuticular forms of resistance against pyrethroids have already been documented and more may emerge, [43,44] so it seems unlikely that the polyflurobenyl-modified pyrethroids alone will provide a panacea to address this “looming public health catastrophe” [43]. Furthermore, recent studies of Aedes aegypti indicate that physiological resistance to the lethal effects of transfluthrin may be associated with concomitantly decreased responsiveness to its repellent mode of action at sub-lethal doses [46]. …”
Section: Discussionmentioning
confidence: 99%
“…Among commercially available active ingredients, DEET remains the 'gold standard' contact repellent (Leal, 2014), although continuous usage can lead to resistance (Pellegrino et al, 2011;Stanczyk et al, 2013;Sugiharto et al, 2016). Similar concerns have been raised for volatile pyrethroids because of widespread kdr resistance to pyrethroid insecticides in the field and, furthermore, reduced sensitivity to transfluthrin was observed in laboratory-selected strains of Aedes aegypti from Belize (Wagman et al, 2015) and Puerto Rico (Agramonte et al, 2017).…”
Section: Introductionmentioning
confidence: 96%